2006
DOI: 10.1073/pnas.0506668103
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal modulation of cellular invasion via TGF-β1 signaling

Abstract: Group A Streptococcus (GAS) and other bacterial pathogens are known to interact with integrins as an initial step in a complex pathway of bacterial ingestion by host cells. Efficient GAS invasion depends on the interaction of bound fibronectin (Fn) with integrins and activation of integrin signaling. TGF-␤1 regulates expression of integrins, Fn, and other extracellular matrix proteins, and positively controls the integrin signaling pathway. Therefore, we postulated that TGF-␤1 levels could influence streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 39 publications
2
61
0
Order By: Relevance
“…For example, uropathogenic E. coli was reported previously to establish quiescent intracellular reservoirs within the urinary bladder epithelium as a mechanism for persistence and a source for recurrent urinary tract infections (27). Group A streptococci appear to upregulate transforming growth factor ␤1 in infected hosts, leading to increased expression of the host cell receptor ␣5␤1 integrin, resulting in enhanced host cell invasion and potentially persistence within the host (34). Anthrax infections can turn latent and become reactivated at a later time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, uropathogenic E. coli was reported previously to establish quiescent intracellular reservoirs within the urinary bladder epithelium as a mechanism for persistence and a source for recurrent urinary tract infections (27). Group A streptococci appear to upregulate transforming growth factor ␤1 in infected hosts, leading to increased expression of the host cell receptor ␣5␤1 integrin, resulting in enhanced host cell invasion and potentially persistence within the host (34). Anthrax infections can turn latent and become reactivated at a later time.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of GAS cell adherence and invasion have been extensively studied and reviewed (Courtney et al, 2002;Kreikemeyer et al, 2004;Cleary, 2006). Several studies have investigated the cellular pathways required for the adherence and uptake process phenotypically (Pancholi and Fischetti, 1997;Miettinen et al, 2000;Ozeri et al, 2001;Purushothaman et al, 2003;Wang et al, 2006) and on the global transcriptome scale (Kobayashi et al, 2003;Nakagawa et al, 2004;Klenk et al, 2005). Particularly, the early steps downstream of host cell adherence and internalization determine the fate of the invaded GAS and the infected cell, and are potentially crucial for the disease outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that GAS can induce TGF-β1 by cultured human tonsil fibroblasts and that exogenous TGF-β1 up-regulates expression of α5β1 integrins and fibronectin, which are required for internalization of GAS by host cells (4). Among the diverse functions of TGF-β1, this cytokine plays a pivotal role in generation of regulatory T cells (Tregs) and T helper (Th) 17 cells (5-7).…”
mentioning
confidence: 99%